Pengaruh Kompetensi Guru Penggerak dalam Meningkatkan Mutu Pendidikan - Samari, Samari (Yayasan Sembilan Pemuda Indonesia, 2022)
Research on the influence of teacher competence on the effectiveness of the “sekolah penggerak” program is still minimal. This study aims to see the effect of teacher competence on the effectiveness of “sekolah penggerak” program in improving the quality of education. This research is a qualitative research with a literature study approach. The results of the study indicate that teacher competence is very influential on the effectiveness of the program that will support the improvement of the quality of education. This research contributes to teachers and education practitioners in explaining the “sekolah penggerak” program and seeing how four teacher competencies play an important role in the program.